Творчі методи навчального проектування у професійній підготовці архітекторів: світовий досвід - Олена Кайдановська (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті розглянуто потенціал навчального архітектурного проектування у формуванні професійної компетентності, креативності, самостійності майбутнього фахівця, у плеканні комунікативних навичок спілкування. Обґрунтовано доцільність використання інноваційних методів навчання з опорою на світовий досвід архітектурної освіти. В статье рассмотрен потенциал учебного архитектурного проектирования в формировании профессиональной компетентности, креативности, самостоятельности будущего специалиста, обосновано необходимость использования инновационных методов обучения с опорой на мировой опыт архитектурного образования. Considering world experience in future architects training, «Architectural design» is the main subject in content of learning, and this subject has significant opportunities for the formation of readiness for creative professional activity in the field of architecture, for educating creative thinking and need for self-development. Creative methods of project work are relevant and required in architectural education, they teach students to independently solve a set of tasks which are important for architectural practice, social and interpersonal communication, professional growth. The purpose of this article is to review creative methods of educational design in world practice and to define possibilities of its implementation in modern architect's professional training. The leading idea of architects professional training at modern stage is conceptual design, which by its essence is maximally close to architectural activity in social space and it already is a component of professional's project culture. Method of conceptual design teaches architecture students to see the world in special professional manner - synthetically, constructively and deeply; it allows to reorganize educational process, to interest students by using such creative methods and approaches as abstraction, systemacy, scenario modeling, compositional solutions variation and stylization. World practice of architectural education makes focus on expansion of student's professional competence; on gaining intellectual, spatial, technical and interpersonal communicative skills; on understanding historical, socio-cultural and environmental context of architecture. Purposive mastering of basics of architectural search creative process, gaining basic experience of independent work in the sphere of design promotes specialist's professional development, teaches to comprehensively solve architectural design problems and to understand architect's role and responsibility towards society.